The reverse relative age effect in professional soccer: an analysis of the Brazilian National League of 2015 - Ramos-Filho, Luiz (2020)
Abstract Research question: The relative age effect (RAE) has been examined in several sports, proposing that athletes born in the initial months of each year have an advantage in development compared to those born in the final months. Recent studies reveal a reverse RAE whereby players born at the end of the year reach the adult category with better technical quality, salary and career length than the other players. We analyze whether there is a reverse relative age effect, assessing the influence on the market value and sports performance of soccer players. Research methods: We test the hypotheses on a dedicated dataset of 601 professional Brazilian soccer players that participated in the Brazilian National League in 2015. Brazil is the largest exporter of soccer players to the top leagues and teams. Data were analyzed using multivariate statistics and the Pearson chi-square test. Results and findings: We found a reverse relative age effect in relation to the players’ sports performance, but not in relation to their market value. Implications: Players born in the last months of the year had better sports performance. We contribute to a better understanding of the reverse effect of relative age, accounting for individual characteristics and career trajectory, with potential implications for better decisions by soccer coaches and managers regarding how soccer players are selected and developed.